Second sight : the visionary imagination in late Victorian literature - Maxwell, Catherine, 1962- (Manchester, U.K. ; New York : Manchester University Press ; New York : Distributed in the USA exclusively by Palgrave Macmillan, 2009)
An innovative reassessment of late Victorian literature in its relation to visionary Romanticism. It examines the subject in relation to a range of writers of the period, including Pater Rossetti, Hardy and Vernon Lee.
9780719071447; 9780719071447; Cover; Contents; Acknowledgements; A note on the texts; Introduction; 1 'An aching pulse of melodies': Dante Gabriel Rossetti's poetic magnetism; 2 Walter Pater's 'strange veil of sight'; 3 Of Venus, vagueness, and vision: Vernon Lee, Eugene Lee-Hamilton, and 'the spell of the fragment'; 4 Theodore Watts-Dunton's Aylwin and the reduplications of Romanticism; 5 Thomas Hardy's poetry: 'the intenser stare of the mind'; Index.
Includes bibliographical references (pages 232-251) and index.
eBooks on EBSCOhost
Keywords: English literature -- 19th century -- History and criticism; Romanticism; Littérature anglaise -- 19e siècle -- Histoire et critique; Romantisme; romanticism (form of expression); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English literature; Romanticism; 1800-1899; Criticism, interpretation, etc